THEORETICAL AND LEGAL ANALYSIS OF APPROACHES TO THE DEFINITION AND CHARACTERISTICS OF COUP D’ETAT AS TECHNOLOGY TO DESTABILIZE SOCIAL AND POLITICAL SYSTEM IN THE CONTEXT OF STRATEGY OF RESPONSE DEVELOPMENT - Onyshchenko O.A. (Pressing Problems of Public Administration, 2016)
The article deals with the analysis of theoretical and methodological approaches to the de nitions andcharacteristics of state coups as a type of destabilization technologies of the socio-political system ofthe state in the context of national security. The necessity of a systematic approach to the de nitionof prerequisites and prediction of consequences of the destabilization policies of social and politicalsystems in order to develop public response methods.